A Comparison of Perioperative Morbidity, Perioperative Mortality, and Disease-Specific Survival in Elderly Women (≥70 Years) Versus Younger Women (<70 Years) With Endometrioid Endometrial Cancer. Issue 5 (1st July 2009) - Vaknin, Zvi; Ben-Ami, Ido; Schneider, David; Pansky, Moty; Halperin, Reuvit
Abstract : Objective: The study compares the perioperative morbidity and mortality rates of elderly (≥70 years) and younger (<70 years) patients with endometrioid endometrial cancer. Methods: The study cohort consisted of 115 consecutive women undergoing explorative laparotomy because of endometrioid endometrial cancer. Clinical data included patients' age, comorbidities, chronic use of medications, body mass index (kg/m 2 ), previous surgical procedures, surgical International Federation of Gynecology and Obstetrics stage, histological grade, relevant prognostic factors, a number of dissected lymph nodes, occurrence of perioperative complications, postoperative hospital stay (in days), and long-term disease-specific survival (in months). Results: Patients were divided into 2 groups: those younger than 70 years (group 1: 84 women, 73%) and those 70 years or older (group 2: 31 women, 27%). Although, as expected, elderly women had more major comorbidities, the rate of perioperative complications was similar between the 2 groups. In a logistic regression model, only chronic lung disease, gastrointestinal disease, and past abdominal surgery correlated with a higher rate of perioperative complications. None of the cohort patients died during the perioperative period. The long-term disease-specific survival was significantly poorer for the older group. Conclusion: Chronological age by itself should not be a contraindication for the proper surgical treatment of elderly women with endometrioid endometrial cancer, because it is a poor predicting factor for perioperative morbidity and mortality.